Electromyographic activity of shoulder muscles on two preventive exercise programmes for swimmer`s shoulder: elastic band versus weight - Tavares, N.; Vilas-Boas, J. P.; Castro, M. A. (Sports Biomechanics, 2025)
Strength programmes have shown good results in preventing swimmer`s shoulder. However, there aren`t studies based on electromyographic (EMG) analysis in these programmes. This study aims to compare an EMG activity of the middle trapezius (MT), lower trapezius (LT), infraspinatus (IS), serratus anterior (SA), and pectoralis major (PM) in two swimmer`s shoulder preventive programmes - one performed with elastic band and the other with weights. Twenty competitive swimmers performed two strength programmes consisting of five exercises each, while the analysis of EMG activity in MT, LT, IS, SA, and PM for each exercise was recorded. The superficial EMG was used to collect data at a sampling frequency of 1000 hz. The Paired Sample T-test or the Wilcoxon test was applied to compare EMG activity between programmes. The internal rotation at 90º (p < 0.001) and external rotation at 90º (p = 0.01) exercises produced high myoelectric shoulder muscle activity with an elastic band. Conversely, scapular punches (p < 0.001) exercise has high shoulder EMG activity when performed with weights. Performing the same preventive exercise programme with two different instruments produces great variability in the myoelectric activity of the shoulder muscles.